Keynesian versus Marxian Explanations of the Financial Crisis. Issue 1 (2nd January 2016) - Hossein-zadeh, Ismael
ABSTRACT: Many Keynesian economists envisioned a new dawn of Keynesianism in the 2007–8 financial meltdown in the United States. Nearly seven years later, it is clear that the much-hoped-for Keynesian prescriptions are completely ignored. Why? Keynesian economists' answer: "neoliberal ideology, " which they trace back to President Reagan. This study argues, by contrast, that the rise of neoliberalism has much deeper roots than pure ideology, that the transition from Keynesian to neoliberal economics started long before Reagan was elected president, and that the Keynesian reliance on the ability of the government to regulate and revive the economy through policies of demand management rests on a wishful/optimistic perception that the state can control capitalism. The study further argues that the Marxian theory of unemployment, based on his theory of the reserve army of labor, provides a much more robust explanation of the protracted high levels of unemployment than the Keynesian view, which attributes the plague of unemployment to the "misguided policies of neoliberalism." Likewise, the Marxian theory of subsistence or near-poverty wages provides a more cogent account of how or why such poverty levels of wages, as well as a generalized predominance of misery, can go hand-in-hand with high levels of profits and concentrated wealth than the Keynesian perceptions, which view high levels of employment and wages as necessary conditions for an expansionary economic cycle.